Analisis Kritis Critical Book Review Buku Ajar Anatomi Fisiologi Karya Heni Puji Wahyuningsih dan Yuni Kusmiyati - Gea, Fifitriani; Lahagu, Albertus; Hulu, Adil Hati; Halawa, Desheriasti; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Critical book review is one of the mandatory assignments given to students to review a book in the sense of focusing on evaluation (explanation, interpretation, and analysis) of the book's strengths and weaknesses and how the book affects the way of thinking and increases understanding of a field of study. Teaching materials for Physiological Anatomy by Heni Puji Wahyuningsih and Yuni Kusmiyati are a comprehensive learning resource to understand the structure and function of the human body. This book discusses various organ systems in detail, from the cellular to the macroscopic level. Its clear explanations and informative pictures make this book easy for readers to understand. This study aims to find out the discussion of teaching materials in detail. This study uses a literature study method, namely collecting data from various literature or scientific references and physiological anatomy books. The results of the critical analysis of the research are teaching materials discussing the physiological anatomy of the human body, where anatomy is the study of the structure and relationships between body parts of living things, and physiology is the study of the study of the function of body parts